2019
DOI: 10.1016/j.hlpt.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic replacement therapy for lysosomal storage disorders: Drug evaluations review in Spain

Abstract: Introduction: In the European Union companies only need to demonstrate that the risk-benefit balance of the new drug is favourable to obtain the authorization to sell new drugs. Hence a comparison with available treatments, a cost-effectiveness analysis and the place in the therapy of the new drug are not required. Therefore, it is necessary to carry out these analyses in an additional study. In Spain there is no national government agency, which conducts a centralized evaluation and makes decisions on funding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…This issue of Health Policy and Technology contains an article by Darba et al that describes what they found in Spanish reports of the efficacy and safety of treatments for rare lysosomal storage diseases (LSDs) like mucopolysaccharidosis (MPS), Gaucher disease, Fabry disease and Pompe disease. [1] Based on their findings, it seems that the treatments for LSDs work to differing degrees in different subgroups and that the evidence of their effectiveness varies substantially. The authors note that new methods to assess effectiveness are needed since the current methods will not be very feasible in cases where just one subgroup of patients with a rare disease represents the entire target population.…”
mentioning
confidence: 99%
“…This issue of Health Policy and Technology contains an article by Darba et al that describes what they found in Spanish reports of the efficacy and safety of treatments for rare lysosomal storage diseases (LSDs) like mucopolysaccharidosis (MPS), Gaucher disease, Fabry disease and Pompe disease. [1] Based on their findings, it seems that the treatments for LSDs work to differing degrees in different subgroups and that the evidence of their effectiveness varies substantially. The authors note that new methods to assess effectiveness are needed since the current methods will not be very feasible in cases where just one subgroup of patients with a rare disease represents the entire target population.…”
mentioning
confidence: 99%